Estela Salomina Momot Pengaruh Pemberian Ekstrak Daun Malaka (Phyllanthus emblica L.) Terhadap Kadar Kolesterol Total Mencit (Mus musculus) Betina Dengan Diet Tinggi Lemak Jenuh: PENGARUH PEMBERIAN EKSTRAK DAUN MALAKA (Phyllanthus emblica L.) TERHADAP KADAR KOLESTEROL TOTAL MENCIT (Mus musculus) BETINA DENGAN DIET TINGGI LEMAK JENUH - Estela Momot; Novrina Situmorang; Inda M.H. Sinaga; Surjadi Rimbun; Sanggam B. Hutagalung (Jurnal Kedokteran Methodist, 2024)
Abstract Background: cholesterol is a fatty substance circulating in the blood, yellowish in color and in the form of wax, which is produced by the liver and is needed by the body. High cholesterol increases a person's risk of developing narrowing of the arteries or atherosclerosis, blood clots in certain parts of the body, strokes and heart attacks. One plant that is thought to have antihypercholesterol activity is Malacca leaf (Phyllanthus emblica L.). Malacca leaf extract works as an inhibitor of the enzyme 3-hydroxy-3-methyl-glutaryl coenzyme A reductase (HMG-CoAR) so that cholesterol synthesis decreases. Objective: to determine the effect of Malacca leaf extract (Phyllanthus emblica L.) on total cholesterol levels in mice (Mus musculus) females with a diet high in saturated fat. Methods: this study is experimental laboratory using the design method of Randomized control group pretest & post test design. Samples in this study using mice (Mus musculus) female sex. Mice are divided into 4 groups, namely P0, P1, P2 and P3. Group P0 was given standard feed, Group P1 was given standard feed and quail egg yolk, group P2 was given standard feed, quail egg yolk and Malacca leaf extract, group P3 was given standard feed, quail egg yolk and orlistat drug. Results: the average percentage of increase in total cholesterol levels in the group given Malacca leaf extract has a percentage of increase in total cholesterol levels is smaller than the other groups of 3%. Conclusion: the administration of Malacca Leaf Extract can prevent the increase in total cholesterol levels in mice.